Collective experience of precarity and civil movements - Dmitriy A. Khoroshilov; Ekaterina A. Hilger (Национальный психологический журнал, 2019)
Background. Thestudy explores the potential predictors of the collective action in the context of contemporary social and civil movements. Classical socio-psychological models of social movements focus on the concept of social identity, i.e. collective identity and have difficulty explaining a sudden upsurge of popular demonstrations in the world (from mass demonstrations in Russia till “Yellow vests” movement in France). Objective. The research aims to identify a latent criterion of the identification with the protest movement which can be situated within the social space only at the moment of people assemblies. Design. According to the literature review, the authors suggest that the collective experience of precariousness, representing the people’s vulnerability in existing social and political order can be a latent identification criterion of social and civil movements. In the research, we subjected the data of semi-structured interviews with the activists of Russian civil movements to the Jonathan A. Smith’s method of interpretative phenomenological analysis. Findings. As a result of the qualitative analysis of the interviews, the main features that manifest the collective experience of precariousness were identified. The collective experience is performed through the views of the civil movements activists in Russia in the 2010s: 1) Participation in demonstrations s identified with the particular state; 2) Experience of injustice as stepping out the comfort zone; 3) Intention to change social order; 4) Handling the fear of punishment; 5) Deception and lost illusions. Conclusion. Precarity becomes a predictor of collective action only in the case if it becomes a collective experience of a community, a formal assigning to the precariat class is not enough for collective mobilization. The understanding of how the collective experience of precariousness is identified with new social movements uncovers perspectives for further research.